Air infiltration rate distributions of residences in Beijing. (October 2015) - Shi, Shanshan; Chen, Chen; Zhao, Bin
Abstract: Air change rate is a very important parameter for indoor air quality estimation as it influences the exchange of air pollutants between indoor and outdoor environments. Consequently, determining air change rate distribution is indispensable for assessment of a population's exposure to air pollutants. In this study, the annual and seasonal average infiltration rates (air change rate for window close conditions) of 180 representative residences were simulated using the multi-zone network airflow model (CONTAM) to understand the residential infiltration rate distributions in Beijing. The representative residences were selected by probability sampling based on building characteristics, including building type, floor area, number of rooms, construction year, number of floors, and building orientation. The results show that the annual average infiltration rates in Beijing range from 0.02 to 0.82 h −1 with a median value of 0.16 h −1 . The empirical distributions of the annual and seasonal average residential infiltration rates in Beijing were provided. The annual average infiltration rates were also found to well fit a two-parameter lognormal distribution, the median and standard deviation of which is −1.79 and 0.62. Infiltration rates of 34 residences in Beijing were measured via the CO2 decay method, and the measured infiltration rates of residences matched the simulated distribution well. The differences between the simulated and measured infiltration rates are discussed. Highlights: Residential infiltration rate distributions in Beijing were studied by CONTAM. The results have high potential for use in population exposure assessment. The methodology can be extrapolated for other cities in China.